Modeling of a Highly Sensitive Lorentz Force-Based CMOS-MEMS Magnetometer for E-Compass Applications - Al-Mahdi, O.L.Q. (Institute of Electrical and Electronics Engineers Inc., 2021)
Magnetometers are devices used to measure the magnetic field, however, most commercialized magnetometers are facing several disadvantages. If not being of low sensitivity, the device attains a high cost and high-power consumption. Thus, it is a necessity to mathematically design and model CMOS-MEMS magnetometer which will be able to detect low magnetic fields. A fine simulation using ConventorWare software is applied to validate the designed magnetometer model. In this paper, Lorentz force and an integration of CMOS and MEMS technologies were implemented The designed magnetometer is made in one mode (out-of-plane) to function in one axis (z-axis), and the CMOS-MEMS magnetometer output signal is determined by piezoresistive sensing technique as piezoresistors are connected in full Wheatstone bridge circuit. A 3-D solid model was created and meshed based on the theoretical calculations and data. Simulation results shows that theoretical and simulation results are almost the same, except that resonance frequency is of 11 difference and 11.6 for quality factor. The average percentage difference between calculated and simulated displacement when magnetic field is detected to be of 2.801. Â© 2021 IEEE.